Health-related needs of the displaced population due to armed conflict in Bogota (2003)
Background: The displacement of populations as the result of an armed conflict generally entails a worsening of the living and health conditions of those undergoing such a displacement. This paper is aimed at analyzing the health-related needs perceived by men and women displaced by the armed conflict and their main strategies to address those needs. Methods: A qualitative study was carried out by means of semistructured individual interviews to 31 displaced men and women in the transition stage. A narrative analysis of the contents was conducted, segmenting the information by age and sex. The area under study was made up of five localities in the city of Bogotá. Results: The negative effects on their mental health and psychosocial stability, access to food and, to a lesser degree, gastrointestinal and respiratory disorders, are the main health problems reported by both groups of informants. The difficulty of accessing health care services comes up as an added problem. The precarious economic situation underlies the health care-related needs and problems. To solve their health problems, in addition to the health care services, they employ other strategies within their reach. Expressed needs are coherent with the problems perceived. Some differences between women and men and age groups were observed concerning the definition of the problems and employed strategies. Conclusion: In the health field, actions are required in order to improve their access to services in addition to specific strategies for the psychosocial rehabilitation of the displaced population which take into account the differences existing within this group.